Dynamic carrier transport modulation for constructing advanced devices with improved performance by piezotronic and piezo-phototronic effects: a brief review. (3rd July 2017) - Guo, Zhen; Pan, Haixi; Li, Chuanyu; Zhang, Lili; Yan, Shuai; Zhang, Wei; Yao, Jia; Tang, Yuguo; Yang, Hongbo; Wu, Yihui; Feng, Liping; Zhou, Lianqun
Abstract: Carrier generation, transport, separation, and recombination behaviors can be modulated for improving the performance of semiconductor devices by using piezotronic and piezo-phototronic effects with creating piezopotential in crystals based on non-centrosymmetric semiconductor materials such as group II–VI and III–V semiconductors and transition metal dichalcogenides (TMDCs), which have emerged as attractive materials for electronic/photonic applications because of their novel properties. Until now, much effort has been devoted to improving the performance of devices based on the aforementioned materials through modulation of the carrier behavior. However, due to existing drawbacks, it has been difficult to further enhance the device performance for a built structure. However, effective exploration of the piezotronic and piezo-phototronic effects in these semiconducting materials could pave the way to the realization of high-performance devices. In general, the effective modulation of carrier behavior dynamically in devices such as light-emitting diodes, photodetectors, solar cells, nanogenerators, and so on, remains a key challenge. Due to the polarization of ions in semiconductor materials with noncentral symmetry under external strain, a piezopotential is created considering piezotronic and piezo-photoronic effects, which could dynamically modulate charge carrier transport behaviors across p–n junctions or metal–semiconductor interfaces. Through a combination of these effects and semiconductor properties, the performance of the related devices could be improved and new types of devices such as piezoelectric field-effect transistors and sensors have emerged, with potential applications in self-driven devices for effective energy harvesting and biosensing with high sensitivity, which are different from those traditionally designed and may have potential applications in strained triggered devices. The objective of this review is to briefly introduce the corresponding mechanisms for modulating carrier behavior on the basis of piezotronic and piezo-phototronic effects in materials such as group II–VI and group III–V semiconductors and TMDCs, as well as to discuss possible solutions to effectively enhance the performance of the devices via carrier modulation.